PROSPECTS OF COMPETITIVE AND SUSTAINABLE DEVELOPMENT OF BUFFALO LIVESTOCK IN SOUTH SULAWESI - Islamiyati, Rohmiyatul; Rasjid, Sjamsuddin; Asriany, Anie; Yuliati, Farida Nur (Proceeding Buffalo International Conference, 2013)
Buffalo is one of the potential livestocks to be developed to support of the achievement of meat self sufficiency program in 2014. Buffalo population in South Sulawesi was 130,100 head in 2010 and 96,500 head in 2011 or decreased about 25.83%. Â Buffalo population in Indonesia was 1,999,500 head in 2010 and 1,304,900 head in 2011, or population decreased about 34.74%. Cause of the population decrease was slaughter of productive females but also a relatively long reproductive period. Â Factors supporting the development of buffaloes in South Sulawesi was abundant feed resources, especially from food crop by-product, feed technology, human resources and high market potential (meat and ceremonies).